Sexuality in the elderly under the view of Occupational Therapy (Research, Society and Development, 2022)
With the growth of the elderly population, proportional demands arise, highlighting the needs to provide this public with quality of life in all areas, thus impacting the subject's daily activities. Among the intrinsic needs is the discussion about sexuality, since the subject is considered censored in our culture and even within the health services. The present article aimed to investigate how the literature approaches the sexual health of the elderly and its repercussions, as well as the main factors that can contribute to the neglect of sexual health in old age seen from the perspective of Occupational Therapy. Methodologically, it is a scope review that has great use for research, with searches carried out from national and international databases. One thousand eight hundred and sixty-three articles were found and after reading and analysis, articles that did not meet the previously established inclusion criteria were removed and 10 articles were elected for this review. The studies showed that most of the elderly have numerous potentialities about the expressions of their sexuality, however, after this research, there was a lack of discussions on the subject, including among the elderly. Dependence, loss of autonomy, feeling of incomprehension, taboo, feeling of loneliness and decreased functionality were identified as factors that most contribute to the neglect regarding the subject. The present study does not exhaust the discussion on the topic of sexuality in the elderly population and has contributed to the current scientific construction on the subject.